Antibiotics Utilization and Adherence Pattern in Ajman/UAE - Nehad M. Hamoudi,Jyothi Vanama, Istabraq Dhia Al Ayoubi (Journal of Applied Pharmaceutical Science)
Antibiotic (AB) consumption in UAE is rising with physicians prescribing these drugs for simple ailments like common cold and sore throat. The aim of this work is to identify the utilization pattern of AB in UAE to determine patient’s perspective and involvement in the use and abuse of AB and to estimate people awareness about AB abuse and its complication. A validated, self-administered questionnaire was used for data collection. Data was analyzed by using descriptive statistics and chie-square test when applicable. This cross sectional study was carried out among subjects procuring AB from GMC pharmacy, GMC hospital and community pharmacies located in Ajman. Two hundred and thirty three subjects were participating in this study, 58.8% female and 41.2% male. Majority of participants were Asian and more than forty years old. 41% of participants have purchased AB without doctor’s prescription and 56% of the lot didn’t seek pharmacists advise. About 25% use AB that purchased previously and 19.7% switched over to another AB if symptoms not relieved. 44.2% use AB for cold or running nose and 26.6% for respiratory tract infection. There was a marked preference to the use of augmentin and amoxicillin followed by cefuzime and erythromycin. Participants’ adherence to AB therapy was poor. Results showed a significant association between participants occupation and subjects adherence to AB therapy (P
Keywords: Antibiotic,Utilization,Misuse,Adherence,Knowledge,Complication.